Reviewing Consumer Preference of Online Hotel Booking Services in India - C. Shalini (AG Volumes, 2022)
This research aims to examine the preferences of Indian consumers for online hotel booking services. A surge in travel booking platforms in India has made it easier for clients to book hotels and lodging. For the most part, hotel and travel websites provide travel and lodging packages, in addition to providing transportation and lodging booking interfaces. Attractive deals, usually a bundle of services, and the simplicity of booking are what entice clients to use the hotel site. We found that the convenience of online hotel bookings over offline or via a travel agency is due in large part to features including structural equation, advance booking, discounts, and the ability to reserve rooms at lower prices.